Study of Waste Reduction through Climate Village Program (Proklim) in Malang City - Lailia Yuslichati Rahmadani; Anthon Efani; Setyo Tri Wahyudi; Dini Atikawati (Postgraduate, University of Mataram, 2025)
Waste is a critical problem that needs to be resolved immediately. Based on its source, the largest waste generation in Malang City comes from the domestic sector. So that there needs to be an effort to resolve this by involving the household sector. The purpose of this study was to calculate the level of waste reduction at the location of the climate village program (Proklim) in Community Association (RW) 07 Lesanpuro Village, Malang City. The research method used is the quantitative descriptive method. Data collection techniques through field measurements, observations, and interviews. Data analysis techniques using the calculation formula of waste generation waste composition, waste density, and waste reduction. Total waste reduction was calculated by mass balance analysis. The results showed that average amount of waste generation was 0.388 people/day (kg). The average density of waste is 152.38 kg/m3. The composition of waste is dominated by organic waste, which is 71.63%. The total reduction rate is 20.51% (organic waste is 16.03%, inorganic waste is 4.48%). This amount is not yet by the Jakstranas target of 30% by 2025, although the research location is included in the Proklim category so it is required to optimize waste management by the community.